Asian Drinking Cultures in New Zealand: A Scoping Review - Adams J; Wong G; Zhao IY; Saravanakumar P; Holroyd E; Neville S (SAGE Publications Inc)
Alcohol use causes harm across most populations. However, comparatively little research and policy attention has been paid to drinking cultures among Asian people. A scoping review was undertaken to identify drinking patterns, alcohol-related harm, drinking culture among Asian youth, young adults, and adults living in New Zealand. A search of literature identified 39 relevant outputs. The findings indicated that Asian people enjoy a comparative health advantage when compared with non-Asian population groups through lower rates of alcohol consumption, less risky drinking, and experiencing less harm from drinking. Despite these advantages, the results identified areas where improvements with Asian people’s relationships and experiences with alcohol may be warranted. It is important to develop targeted approaches to Asian drinking that can build on the current whole population-level alcohol initiatives. Further research is warranted to identify specific and additional strategies to address problematic alcohol use in this cohort.
Keywords: 1302 Curriculum and Pedagogy; 1608 Sociology; 1699 Other Studies in Human Society